ANALISIS PERFORMANSI VERY SMALL APERATURE TERMINAL (VSAT) PENGIRIMAN DATA CUACA PENERBANGAN MENGGUNAKAN COMPUTER MESSAGE SWITCHING SYSTEM (CMSS) - ., Hendry Ramonyaga (Faculty of Engineering, Universitas Tanjungpura, 2016)
Pontianak Supadio Meteorological Station is a weather observation station belonging Meteorology and Geophysics Agency in charge of weather observations in the region of West Kalimantan. The data obtained from the weather observation at garden tools contained in Pontianak Supadio Stamet transmitted using VSAT network technology. On the VSAT network, frequent problems of significant delay and capability VSAT terminal while sending and receiving data extremely vulnerable to climate change. VSAT network performance monitoring process and emphasize the value parameter measurement delay and data rate with the method of observation. From the analysis on the scale of value can be a minimum average delay of 624 ms with an average value of a maximum of 1442 ms. As for the value of the maximum data rate that can be as big as 10 Mbytes within 160 seconds. With a delay value and the data rate that has been in the can, VSAT still can communicate well, this is because the VSAT is a feature of TCP spoofing. Process information to predict the weather in Pontianak Supadio Statmet that happens to agencies, airline and everyday life an area by using CMSS. Preliminary data on the observation code identifying synoptic form of a numerical model that describes the weather situation is happening as WIOO (area code Pontianak), 240524Z (delivery time), 070330KT (wind direction and speed in knots), 9999 (visibility flat above 10 km or more), BKN024 (2400 ft broken clouds covering the sky 5/8 to 7,8 part), 33/20 (surface temperature = 33 degrees and the dew point = 20 degrees), Q1009 (air pressure = 1009 mb), NOSIG = (the weather forecast has not changed). Keywords: VSAT, Delay, Data Rate, Service Level, Data Codes, Observation, Weather